Pore-Facies as a tool for incorporation of small scale dynamic information in integrated reservoir studies - Chehrazi, A.; Rezaee, M. Reza; Rahimpour-Bonab, Hossain (Institute of Physics Publishing, 2011)
In this study, the quantification and incorporation of pore geometry, a qualitative parameter, and a source of dynamic information, will be demonstrated in the integrated reservoir studies. To quantify pore geometry, mercury injection capillary pressure (MICP) curves have been exploited. For each MICP curve, 20 parameters were derived and multi-resolution graph-based clustering was applied to classify the curves into nine representative distinct clusters. The number of clusters was determined based on petrography and cluster analysis. The quantified pore geometry in terms of discrete variable has been called pore-facies, and like electro-facies and litho-facies could be used in facies modelling and rock typing phases of an integrated study. The dependence of dynamic reservoir rock properties on pore geometry makes the pore-facies an interesting and powerful approach for incorporation of small-scale dynamic data into a reservoir model. A comparison among various facies definitions proved that neither litho-facies nor electro-facies is capable of characterizing dynamic rock properties, and the best results were achieved by the pore-facies method. Based on this study, it is recommended that for facies analysis in reservoir modelling, methods based on pore characteristics such as pore-facies, introduced in this paper, be used rather than traditional facies that rely on matrix properties. The next generation of the reservoir models which incorporate pore-facies-based rock types will provide a basis for more accurate static and dynamic models, a narrower range of uncertainty in the models, and a better prediction of reservoir performance.